Social Work Curriculum Review Case Study: Service Users Tell Us What Makes Effective Social Workers - Watters, Elizabeth; Cait, Cheryl-Anne; Oba, Funke (Canadian Social Work Review / Revue canadienne de service social, 2016)
This paper presents the findings from community focus groups, comprised of social service users, and explores the characteristics of effective social workers. Focus groups were conducted as part of a case study to inform a Master of Social Work (MSW) curriculum review at Wilfrid Laurier University’s Faculty of Social Work. Wilfrid Laurier University has two MSW programs—the MSW Aboriginal Field of Study (AFS) and a non-Aboriginal program. The case for this study was the non-Aboriginal MSW program. Ongoing program evaluation that includes feedback from service users honours the knowledge of marginalized communities, and is an accreditation requirement of the Canadian Association for Social Work Education (CASWE). Four focus groups were conducted with a total of 24 individuals who access programs from human service organizations that provide supportive housing, immigrant, or refugee services in the Kitchener-Waterloo area. Service users identified numerous characteristics of effective social workers, including kindness, cultural awareness, and strong communication skills, as well as the need to articulate and address issues of professional suitability. We conclude by querying whether the typical assessment of MSW students’ suitability for the profession is adequate, and provide the AFS wholistic and comprehensive evaluation as an example of an alternative approach to MSW student assessment.